IMPLEMENTASI MEDIA KARTU KATA BERGAMBAR DALAM PENINGKATAN KEMAMPUAN KOSAKATA SISWA DI KELAS 1 MI AL IKHSAN - Fatimah, Nurul; Syahara Ningtias, Ilva; Febriyanti, Wulan; Ani Nur Azizah, Selli (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2025)
The use of media in the learning process must be able to adapt to the demands of the times. The implementation of picture word card learning media is very good for learning at school. The implementation of picture word card media is not only to attract students' attention, but also to improve their memory. The purpose of this study is to describe the implementation of picture word card media in learning at the elementary school level. This research was conducted at MI Al Ikhsan. The method used in this study is qualitative with a case study type. Meanwhile, the data collection technique is through interviews, observations and documentation. The results of the study show that the implementation of picture word card media in improving children's vocabulary is going well, although there are obstacles in its implementation. Teachers implement picture word card media in learning according to the planned steps. carried out through steps; 1) determine the theme, 2) prepare picture card media, 3) introduce letters and vocabulary to students, 4) divide students into various groups.